2020
DOI: 10.1016/j.tree.2020.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal Reduction: Causes, Genomic Mechanisms, and Evolutionary Consequences

Abstract: Recent biological analyses indicate that secondary reduction in dispersal ability is a key driver of diversification across numerous lineages. Here we synthesise emerging data to highlight similarities regarding the causes and consequences of dispersal reduction, across taxa and ecosystems, and the diverse genomic mechanisms underpinning these shifts. Natural selection has acted on standing genetic variation within taxa to drive often rapidand in some cases parallellosses of dispersal, and ultimately geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 113 publications
3
91
0
Order By: Relevance
“…Although estimated extinction rates were higher in nonmigratory galaxiids, consistent with expectations from theory and some empirical tests (Rolland et al 2014;Corush 2019), they were not sufficiently elevated to suppress overall diversification rates. Although our findings are broadly consistent with a wide variety of analyses linking high diversification rates with "dispersal reduction" (Waters et al 2020), including one study of migratory behavior in fishes (Tedesco et al 2017), they directly contrast with the conclusions of some recent empirical studies that suggested migratory behavior leads to higher diversification (Rolland et al 2014;Fuchs et al 2015;Corush 2019;Gómez-Bahamón et al 2020) or has no effect (Kennedy et al 2016). The lower diversification rates for migratory galaxiids could be explained by lower natal philopatry relative to other migratory taxa, perhaps reflecting either unpredictability of freshwater habitat quality-and hence greater benefit of straying-or lower locomotory abilities of the migratory stage in galaxiids: larvae.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although estimated extinction rates were higher in nonmigratory galaxiids, consistent with expectations from theory and some empirical tests (Rolland et al 2014;Corush 2019), they were not sufficiently elevated to suppress overall diversification rates. Although our findings are broadly consistent with a wide variety of analyses linking high diversification rates with "dispersal reduction" (Waters et al 2020), including one study of migratory behavior in fishes (Tedesco et al 2017), they directly contrast with the conclusions of some recent empirical studies that suggested migratory behavior leads to higher diversification (Rolland et al 2014;Fuchs et al 2015;Corush 2019;Gómez-Bahamón et al 2020) or has no effect (Kennedy et al 2016). The lower diversification rates for migratory galaxiids could be explained by lower natal philopatry relative to other migratory taxa, perhaps reflecting either unpredictability of freshwater habitat quality-and hence greater benefit of straying-or lower locomotory abilities of the migratory stage in galaxiids: larvae.…”
Section: Discussionsupporting
confidence: 88%
“…We encourage future investigations of the potential interaction of dispersal ability (accurately measured) and the proximity of suitable habitats on diversification rates, in the context of the "intermediate dispersal" model. More generally, galaxiid fishes also provide a key opportunity to investigate the molecular mechanisms underlining transitions between diadromous and nondiadromous life histories, and whether the multiple transitions observed among galaxiids reflect identical mechanisms, both relative to one another, and to other fishes that have already been investigated in detail (Jones et al 2012;Michalak et al 2014;Terekhanova et al 2014;Lemopoulos et al 2018;Delgado et al 2019;Waters et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to speciation theory, dispersal is a key factor determining the likelihood of speciation in a given geographical area because it influences rates of gene flow across barriers 5,56 . On islands, speciation is most likely to occur when dispersal is high enough to promote island colonisation 8,33 but not so high that gene flow is too frequent 30,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent analyses have highlighted that shifts in animal mobility can have drastic evolutionary consequences (63). The findings of the current study highlight not only the need for rapid olfactory processing in flying insects (2), but also that this sensory ability can be rapidly degraded when no longer required (i.e.…”
Section: Resultsmentioning
confidence: 99%